Increased water storage of Lake Qinghai during 2004–2012 from GRACE data, hydrological models, radar altimetry and in situ measurements. Issue 1 (14th October 2017) - Wang, Linsong; Chen, Chao; Thomas, Maik; Kaban, Mikhail K; Güntner, Andreas; Du, Jinsong
SUMMARY: Terrestrial water storage (TWS) changes in the Tibetan Plateau (TP) are sensitive indicators for water dynamics associated with climate variability. Joint analyses using both GRACE space mission and satellite altimetry data are increasingly being used to monitor TWS. The objective of this study is to confirm that it is possible to reliably monitor water storage changes in large lakes based on integrative analysis of GRACE data. This study focuses on data integrated and analysed for Lake Qinghai located in the northeast TP, and shows a clear continuous water-level rise since 2004. We have developed a simple framework to estimate water storage variations in individual regions using a spatial averaging kernel, while simultaneously minimizing the effects resulting from uncertainties of GRACE data using Land Surface Models (LSMs) and in situ measurements. Water storage anomalies not related to lakes, such as soil moisture, snow and reservoirs, are estimated using GLDAS/Noah and reservoir gauge station for the period 2004–2012. Our results show that the rate of rise in mass of the GRACE-derived TWS (post GLDAS/Noah anomaly removal) is calculated to be 0.27 ± 0.12 cm yr −1, or an average water-level increase rate of 0.20 ± 0.09 m yr −1 after GRACE-derived TWS (i.e. 0.27 ± 0.12 cm yr −1 ) multiplied by 1/1.34 to recover the 'real' mass variation signal using scaling factor method based on basin function from grids of Lake Qinghai from 2004 to 2012, which is equivalent to the volume change 0.86 ± 0.37 km 3 yr −1 and mainly caused by the fast expansion of Lake Qinghai (0.44 ± 0.04 km 3 yr −1 from altimetry/ in situ measurements) and impoundment of Longyangxia reservoir (0.28 ± 0.17 km 3 yr −1 based on the linear height–volume relationship and in situ water-level observations). The residual signal (GRACE−GLDAS/Noah−reservoir−Lake Qinghai) likely reflects the mass leakage from the surrounding lakes in the regions (i.e. Har, Gyaring and Ngoring) and groundwater contributions (i.e. groundwater is not included in GLDAS/Noah) due to the limited spatial resolution of GRACE. The results suggest that the combined use of LSM and GRACE measurements is a useful method for monitoring changes in the mass of large lakes. Additionally, our analysis shows that it is necessary to improve LSM results with in situ forcing parameters and groundwater level data, which will reduce the uncertainty in the application of GRACE data. There is still a need to use complementary models or in situ observations to eliminate the influence of glacial isostatic adjustments and tectonic processes.